Israel's High Fertility Rate and Anemic Skill Acquisition - Assaf Razin (Center for Economic Studies and ifo Institute (CESifo), 2017)
The exceptionally high fertility among ultra-Orthodox Jews, and Arab minority, increasing portions of the population, is the main reason for Israel's flagging labor-force participation. In addition, high fertility diminishes Israel's skill attainment of the labor force. A rise in income inequality in all advanced economies, which in the last two decades has taken a sharp upward turn in Israel, has a potential for setting off social- divide and political polarization.
Keywords: D10; H10; J24; O40; 330